Pengembangan Komitmen Organisasi Pada Karyawan Lazismu (Lembaga Amil Zakat, Infaq dan Sadaqah Muhammadiyah) Kabupaten Gresik: Developing Organizational Commitment Among Lazismu Employees (Muhammadiyah Zakat, Infaq and Sadaqah Collection Institution) Gresik Regency - Maulana, Muhammad Rafi; Saleh, Mohammad; Munir, Akhmad (IJABAH: Indonesian Journal of Sharia Economics, Business, and Halal Studies, 2025)
Organizational commitment is key to the success of Islamic philanthropic institutions that manage public funds based on trust. This study analyzes the condition of organizational commitment and its development strategies among employees of Lazismu Kabupaten Gresik, a zakat institution with a high reputation for accountability and a strong Islamic culture. Using a descriptive qualitative approach through case studies, data was obtained from in-depth interviews, observations, and document analysis, then analyzed using the interactive model of Miles, Huberman, and Saldaña. The results of the study show that the three dimensions of organizational commitment—affective, sustainable, and normative—are formed simultaneously with different drivers. Affective commitment arises from the internalization of spiritual values and the meaning of work as worship, sustainable commitment is influenced by rational considerations such as income stability and career opportunities, while normative commitment is strengthened by a sense of moral and religious responsibility. Lazismu develops employee commitment through the strengthening of spiritual values, a performance-based reward system, employee involvement in decision-making, and the provision of clear career paths. These findings enrich the Three-Component Model of Organizational Commitment with the context of Islamic work ethics, while also confirming the relevance of social exchange theory in faith-based nonprofit organizations. This study provides theoretical contributions and offers a practical model for zakat institutions in designing human resource policies that balance religious values and modern management practices.